ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MODEL ALMAN Z-SCORE PADA PERUSAHAAN SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2018 - Susilawati, Endang (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
This study aims to determine bankruptcy predictions on cement companies listed on the Indonesia Stock Exchange in 2012-2018 using the Altman Z-Score model with the Multiple Discriminant Analysis (MDA) method on five types of financial ratios that have been equipped with cut-off points. i.e. (X1) Working Capital to Amount of Assets, (X2) Retained Earnings to Amount of Assets, (X3) Profit Before Interest & Tax to Total Assets, (X4) Market Value of Equity to Total Liabilities and (X5) Sales to Total Assets. The research approach uses descriptive. The analysis showed that 4 cement companies experienced a decline in financial performance. Z-Score prediction results of PT. Indocement Tunggal Prakasa, Tbk., Not bankrupt. PT. Semen Baturaja Persero Tbk. and PT Semen Indonesia, Tbk entered the gray area. PT Holcim Indonesia Tbk., Is the company with the worst conditions.